Kecenderungan Etnosentrisme, Sikap, dan Intensi Konsumen dalam Membeli Produk Sepatu Buatan Usaha Kecil dan Menengah (UKM) - Nanang Suryadi; Dimas Hendrawan (Jurnal Aplikasi Manajemen, 2012)
This research aims to identify the tendency ethnocentrism, attitudes, and intentions of consumers in buying shoes product which is made by Small and Medium Enterprises (SMEs) using the concept of ethnocentrism. Ethnocentrism is a sociological concept first introduced by Sumner (1906) which refers to attitudes, beliefs, standards, and the excessive behavior of a personfor something in environment. Shimp and Sharma (1987) says that consumers who are etnocentric consumers who have views about the suitability and moral in buying behavior of foreign products.The sample for this research is 232 students Faculty of Economic, University of Brawijaya. Descriptive statistical methods using frequency distribution, cross tabulation method (crosstabs), and chisquare test of independence are used to analyze data. From this research, it found that there is a tendency of ethnocentrism among students of the Faculty of Economics, University of Brawijaya in selecting at a product. The results also showed that students who have a tendency of ethnocentrism, moderate, and non-ethnocentrism have a positive attitude toward Small and Medium Enterprises. This is evidenced by the students intention to buy Small and Medium Enterprises shoes product, but by considering the factors at affordable prices, quality products, attractive models which is up to date, as well as earned income.Keywords: ethnocentrism tendency, attitudes, intentions